2008
DOI: 10.1080/02705060.2008.9664194
|View full text |Cite
|
Sign up to set email alerts
|

Chironomids (Diptera) of Temporary and Permanent Ponds in Central Italy: a Neglected Invertebrate Group in Pond Ecology and Conservation

Abstract: In spite of their ubiquity and the numerous species present in all freshwater ecosystems, chironomids have generally been considered only at the family, subfamily, or tribe level in ecological studies because of the difficulties of specific or generic identification of larvae. We investigated the chironomid communities in 21 astatic ponds in central Italy with the aim of examining the differences between temporary and permanent ponds and within three contrasting mesohabitats. In March, May, and June 2002 we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…On the contrary, composition and abundance of aquatic plants (Waters and San Giovanni, 2002), substrate heterogeneity (Heino, 2000), depth, granulometry composition and oxygen content (Heino, 2000;Brinkhurst, 2002) seem to govern macroinvertebrate distribution in lakes. In contrast, relatively few studies have addressed the spatial distribution of the entire macroinvertebrate communities in ponds and wetlands (Oertli, 1995;De Szalay and Resh, 2000; Van der Meutter et al, 2008), or have been limited to only one taxonomic group (Fairchild et al, 2003;Bazzanti et al, 2008). In particular, three recent studies have dealt with the distribution of macroinvertebrate taxa, their size structure and functional aspects (Della Solimini et al, 2005;Bazzanti et al, 2009) in different mesohabitats (sensu Pardo and Armitage, 1997) of twenty-one temporary and permanent ponds in Central Italy.…”
Section: Introductionmentioning
confidence: 92%
“…On the contrary, composition and abundance of aquatic plants (Waters and San Giovanni, 2002), substrate heterogeneity (Heino, 2000), depth, granulometry composition and oxygen content (Heino, 2000;Brinkhurst, 2002) seem to govern macroinvertebrate distribution in lakes. In contrast, relatively few studies have addressed the spatial distribution of the entire macroinvertebrate communities in ponds and wetlands (Oertli, 1995;De Szalay and Resh, 2000; Van der Meutter et al, 2008), or have been limited to only one taxonomic group (Fairchild et al, 2003;Bazzanti et al, 2008). In particular, three recent studies have dealt with the distribution of macroinvertebrate taxa, their size structure and functional aspects (Della Solimini et al, 2005;Bazzanti et al, 2009) in different mesohabitats (sensu Pardo and Armitage, 1997) of twenty-one temporary and permanent ponds in Central Italy.…”
Section: Introductionmentioning
confidence: 92%
“…Overall, 123 samples of macroinvertebrates proved suitable for analysis. A more detailed description of the sampling methods can be found in Della , Solimini et al (2005) and Bazzanti et al (2008).…”
Section: Sampling and Laboratory Methodsmentioning
confidence: 99%
“…Due to their drastic numerical decrease caused by urban and agricultural practices, ponds are studied for several aspects related to biodiversity patterns as a function of environmental conditions (i.e. Bazzanti et al, 2000Bazzanti et al, , 2003Bazzanti et al, , 2008Batzer et al, 2004;Studinski and Grubbs, 2007;Della Bella et al, 2005, 2007, and for the assessment of their conservation value (Collinson et al, 1995;Oertli et al, 2002;Nicolet et al, 2004;Solimini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…527 Similarly, sympatric cryptic Pipistrellus species in the UK 528 partition their foraging habitat to the extent that P. pipi-529 strellus actively avoids riparian habitats, which are pre-530 ferred by P. pygmaeus, despite their greater insect resource 531 value (Nicholls and Racey 2006). 532 Although the diversity of Dipterans increases with pond 533 area and hydroperiod (Bazzanti et al 2006), some species 534 may be found exclusively in lower volume, shorter-lived…”
mentioning
confidence: 99%